Comparion Of Doppelplates And Functional Magnetic Appliances İn Treatment Of Class II Division 1 Malocclusions - Kerim Ertürk; Aynur Aras (Galenos Yayinevi, 1999)
The aim of this study was to compare the effects of treatment in Class II Div. I malocclusions, using functional magnetic appliances and doppelplates in the same length of time. This study was conducted on a total of 30 patients. From the treatment groups, 10 patients received functional magnetic appliances and the remaining 10 received doppelplate treatment. The control group included 10 untreated patients. The findings that were obtained from the lateral cephalometric radiograms taken at the beginning and at the end of the one year treatment!control periods were statistically evaluated. In both treatment groups significant decrease was observed in ANB angle, I-SN angle, overjet and overbite compared to control group. No significant difference was found between the two methods of treatment.